Induction treatment of ANCA-associated vasculitis with a single dose of rituximab. - LITTLE, MARK (My University, 2014)
Abstract OBJECTIVES: Rituximab is effective in inducing remission in ANCA-associated vasculitis (AAV), with randomized evidence to support its use as four infusions of 375 mg/m(2) (the conventional lymphoma dosing schedule). As B cell depletion (BCD) appears to occur very rapidly after the first dose, we questioned the need for repeat dosing and adopted a standard single-dose protocol of 375 mg/m(2) to treat active AAV. METHODS: All consecutive cases with newly diagnosed or relapsing AAV for whom conventional immunosuppression was contraindicated or ineffective were enrolled. All were rituximab naive. Circulating CD19(+) B cells and clinical and serological markers of disease activity were recorded at regular intervals. Complete remission (CR) was defined as the absence of clinical features of AAV with a prednisolone dose <10 mg/day. RESULTS: Nineteen patients were included, 17 (89%) with generalized disease and 2 (11%) with severe disease (creatinine level >500 μM). Eight (42%) were on additional immunosuppression at the time of rituximab treatment. Satisfactory BCD (<0.005 cells/μl) was achieved in 89% of patients after a median of 13 days. Three-month BCD probability was 89%. Median time to CR following a single dose of rituximab was 38 days and the 3-month probability of CR was 80%. Median time to B cell repopulation was 9.2 months and to disease relapse/redose was 27 months. Use of this single-dose protocol saved an estimated £4533/patient (US$7103; €5276) compared with a 4 × 375 mg/m(2) dosing schedule. CONCLUSION: Our single-centre experience suggests that a single dose of rituximab of 375 mg/m(2) is a reasonable and more cost-effective therapy for inducing remission in patients with AAV.
PUBLISHED
Keywords: Rituximab; Rituximab